ఆంధ్ర సారస్వత పరిషత్తు వజ్రోత్సవాలు వజ్రోత్సవ సంచిక (27, 28, డిసెంబర్ 2003) - (:unkn) unknown (Andhra Saraswata Parishath, 2003)
It;s about history of Andhra Saraswata Parishathu. It's a special edition on the occassion of its diamond jubliee.
Andhra Saraswata Parishathu Vajraotsavalu vajarothsava Sanchika (27, 28, December 2003
Keywords: Telugu; Literature; Telugu; Telugu